Prevention and long-term outcomes of naturally occurring canine heartworm infection in primary care settings - Mwacalimba, Kennedy; Morrison, Jo Ann; Ly, Patrick; Spofford, Nathaniel; Yang, Mike; Saito, Emi; Sheehy, Jenifer; Adolph, Christopher; Poulsen Nautrup, Barbara; Brennan, Christopher (Frontiers in Veterinary Science, 2024)
Background: This study had two objectives: First, to examine the association between the history of heartworm preventive purchase compliance and the risk of positive heartworm tests, and second to preliminarily investigate the long-term cardiac outcomes of heartworm disease in dogs that had undergone successful adulticidal therapy.A retrospective cohort study design was used for both analyses, using anonymous transaction data from Covetrus (retrospective analysis 1) and anonymized medical records from Banfield Pet Hospital (retrospective analysis 2), both including canine patients across the USA. The first analysis examined the relative risk (RR) of a positive heartworm test in dogs with lapses in heartworm preventive purchase history compared to dogs that had no history of a preventive purchase six to 24 months prior to the test. In the second analysis, a long-term evaluation of structured diagnostic codes pertaining to cardiac diseases and risk assessment of outcomes was performed in dogs that had previously been successfully treated for heartworm disease compared to dogs that never had a positive heartworm test.Results: 83,478 unique patients were included in the first analysis. Compared to 32,413 dogs with no history of a heartworm preventive purchase, 44,410 dogs with lapses in monthly preventive purchases had a reduced risk of testing positive for heartworm disease (RR = 0.36, P < 0.0001). Dogs (n = 6,655) with lapses in injectable heartworm preventive administration had a decreased risk of a positive test versus dogs with no preventive purchases (RR = 0.15, P < 0.0001), as well as versus dogs with lapses in monthly heartworm preventive purchases (RR = 0.28, P = 0.0024). In the second analysis, 6,138 patients treated for heartworm infection were found to have significantly (P < 0.001) elevated risks of right heart failure (RR = 3.59), left heart failure (RR = 1.83), or cardiomyopathy (RR = 2.79) compared to 4,022,752 patients that never had a positive heartworm test.Conclusions: This study highlights the importance of compliance with heartworm preventive guidelines, to reduce the risk of heartworm disease in dogs, which is not only a potentially lifethreatening condition in the short-term but also associated with long-term negative cardiac outcomes.